"Dead as a Dodo": Anthropocene Extinction in the Early Modern World. Issue 1 (March 2023) - Ray, Sugata
Abstract : Among the species that went extinct in the last 500 plus years under colonial regimes, the ill-fated dodo became an early icon of the Anthropocene Extinction. While much has been written on the biotechnological apparatuses that expedited the extinction of the dodo, it was the complicity of Western European imperialism and early modern aesthetic regimes that were responsible for the ecocide of the Anthropocene (read Eurocene) Extinction.